Как свежи были розы в аду: роман / Евгения Михайлова - Михайлова Евгения (Детектив-событие, 2012)
Экземпляры: СФ-5 (20130306) / Инвентарный номер: 41336z5 / Цена: 258.50 / Сис.шифр: 84(2) / Авт.знак: М 69 / ГРНТИ: 17.82.31 / ББК: 84(2=Рус)